Discovery of 4-(2-(dimethylamino)ethoxy)benzohydrazide derivatives as prospective microtubule affinity regulating kinase 4 inhibitors. Issue 34 (27th May 2020) - Khan, Nashrah Sharif; Khan, Parvez; Inam, Afreen; Ahmad, Kamal; Yousuf, Mohd.; Islam, Asimul; Ali, Sher; Azam, Amir; Husain, Mohammad; Hassan, Md. Imtaiyaz
Abstract : Inhibition studies of MARK4 with selected hydrazone derivatives. Abstract : Microtubule affinity regulating kinase 4 (MARK4) is a Ser/Thr kinase, considered as a potential drug target for cancer, diabetes and neurodegenerative diseases. Due to its significant role in the development and progression of cancer, different in-house libraries of synthesized small molecules were screened to identify potential MARK4 inhibitors. A small library of hydrazone compounds showed a considerable binding affinity to MARK4. The selected compounds were further scrutinized using an enzyme inhibition assay and finally two hydrazone derivatives (H4 and H19 ) were selected that show excellent inhibition (nM range). These compounds have a strong binding affinity for MARK4 and moderate binding with human serum albumin. Anticancer studies were performed on MCF-7 and A549 cells, suggesting H4 and H19 selectively inhibit the growth of cancer cells. The IC50 value of compound H4 and H19 was found to be 27.39 μM and 34.37 μM for MCF-7 cells, while for A549 cells it was 45.24 μM and 61.50 μM, respectively. These compounds inhibited the colonogenic potential of cancer cells and induced apoptosis. Overall findings reflect that hydrazones/hydrazone derivatives could be exploited as potential lead molecules for developing effective anticancer therapies via targeting MARK4.